2020
DOI: 10.31235/osf.io/qk6xr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Informal caregiving and quality of life among older adults: Prospective analyses from the Swedish Longitudinal Occupational Survey of Health (SLOSH)

Abstract: Providing unpaid informal care to someone who is ill or disabled is a common experience in later life. While a supportive and potentially rewarding role, informal care can become a time and emotionally demanding activity, which may hinder older adults’ quality of life. In a context of rising demand for informal carers, we investigated how caregiving states and transitions are linked to overall levels and changes in quality of life, and how the relationship varies according to care intensity and burden. We used… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These studies are affected by low engagement and high attrition rates 29 often due to the complexity, time demands and intensity of care-provision. 30 Internet-facilitated interventions have improved access through being flexible and cost-effective. 31 This is further enhanced by the recent proliferation in smartphone ownership, concomitant with availability of mobile applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are affected by low engagement and high attrition rates 29 often due to the complexity, time demands and intensity of care-provision. 30 Internet-facilitated interventions have improved access through being flexible and cost-effective. 31 This is further enhanced by the recent proliferation in smartphone ownership, concomitant with availability of mobile applications.…”
Section: Introductionmentioning
confidence: 99%
“…These studies are affected by low engagement and high attrition rates 29 often due to the complexity, time demands and intensity of care-provision. 30…”
Section: Introductionmentioning
confidence: 99%
“…However, we did find a decrease in life satisfaction for new care-givers who provided care in 2020 but not in 2017. This finding may be connected to a caregivers' recent transition into family care, as prior research has shown that particularly new care-givers experience declines in life satisfaction and quality of life (Sacco et al, 2022;Gerlich and Wolbring, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…Even in non-pandemic times, studies confirm the assumptions underlying the care-giver stress process model (Pearlin et al, 1990) by showing that family care-giving is a persistent cause of stress leading to negative wellbeing outcomes (e.g. Hirst, 2005;Hansen et al, 2013;Kaschowitz and Brandt, 2017;Sacco et al, 2022). Specifically in Germany, which is often considered to have an 'explicitly familialistic' care regime, family care-givers are at the centre of maintaining the health and wellbeing of individuals in need of care (Leitner, 2019;Fischer et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation